Σχεδιασμός. οργάνωση και βελτίωση της ποιότητας και παραγωγικότητας του 3ου ΣΠΤΧ της ΕΦ - Κουρτούλας, Θουκυδίδης (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This particular dissertation focuses on the design, organization and improvement of the quality and productivity of the 3rd WAT (Workshop Area Technical) lab. The 3rd WAT is one the most important units of technical support for the National Guard and is based at the « Capt. Eumenios Panagiotou» camp, in Polemidia Limassol. The study of this dissertation was based on two pillars: the quality control and the production management. Based on the theoretical concepts of these two large subjects, an effort was made towards a research elaboration and use of different error detection methods but also the finding of practical solutions. In the first stages of the dissertation different tools of Statistical and Quality Control were used, such as cause and effect diagrams (fishbone type diagrams), included in the diagrams there was brainstorming, so as to lead to findings and sorting of the main errors that are highlighted in practice and are connected with the dissertation topic. Moreover, some suggestions were stated and pointed out by the working staff. With a large number of partial measurements (eg. dimensions) in different time frames and sampling mainly from the CNC machine productions, which is the main department of the workshop equipment, the ability of the machines was confirmed as far as how effective they are and their humane productivity abilities, meaning how able they are to produce portions within specification guidelines. In addition, an investigation took place concerning the processes and whether they followed the statistical control. At the same time, the quality control research data was collected concerning the production management issue. After careful deliberation with the working staff, it was immediately evident that there were many issues towards solving mainly the organization and production of the 3rd WAT labs. Using different methods of production management modern theories, ways of improvement and increase of productivity in the lab using mathematical calculations based on simple and common knowledge were found. It is also worth mentioning, that there has been a small reference to damage issues, and in the ways of eradication and the whole preventive maintenance with the use of various forms. Finally, improvement suggestions were made towards the comfort and workforce laws within the workspace; a piece integral to the Quality control. Astoundingly, from this dissertation the 3rd WAT benefited as much as the researcher, as this topic was of broad sense based on a variety of theoretical concepts, but with practical and essential results.
Keywords: Quality control; Statistical and process control; Production management; Production system; Preventative maintenance; Lab- workshop; Quality tools; Ποιοτικός έλεγχος; Στατιστική και έλεγχος διεργασιών; Διοίκηση παραγωγής; Παραγωγικό σύστημα; Προληπτική συντήρηση; Εργαστήριο- μηχανουργείο; Εργαλεία ποιότητας